1998
DOI: 10.1557/jmr.1998.0405
|View full text |Cite
|
Sign up to set email alerts
|

Textures of thin copper films

Abstract: The textures of thin copper films were determined quantitatively by measuring (111) pole figures with x-ray diffraction. Measurements were performed on a variety of samples, differing in copper film thickness and deposition technique, diffusion barrier material, and the presence or absence of a cap layer. Texture changes due to an annealing treatment were also recorded and correlated with stress measurements by the wafer-curvature technique. It is found that the deposition method (PVD vs CVD) has a strong effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 10 publications
0
17
1
Order By: Relevance
“…For copper, 50% of the grains may be {111} oriented, 15% of the grains {001} oriented, with the remainder randomly oriented [12,13]. In copper, it was noted that the population of {111} and {001} textures remains relatively constant even after multiple thermal cycles [12,13]. The presence of a {001} sub-texture is also noted in some studies of gold [2,6].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For copper, 50% of the grains may be {111} oriented, 15% of the grains {001} oriented, with the remainder randomly oriented [12,13]. In copper, it was noted that the population of {111} and {001} textures remains relatively constant even after multiple thermal cycles [12,13]. The presence of a {001} sub-texture is also noted in some studies of gold [2,6].…”
Section: Introductionmentioning
confidence: 91%
“…Recent studies of FCC thin metal films indicate a strong {111} texture along with a secondary {001} texture. For copper, 50% of the grains may be {111} oriented, 15% of the grains {001} oriented, with the remainder randomly oriented [12,13]. In copper, it was noted that the population of {111} and {001} textures remains relatively constant even after multiple thermal cycles [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Hence, different barrier systems should also lead to changes of both initial PVD and ECD Cu texture. The present paper will discuss the effect of various barrier layers on the initial microstructure of PVD and freshly electroplated Cu thin films.…”
Section: Introductionmentioning
confidence: 99%
“…For Al interconnects, a ͑111͒ fiber texture and bamboo-like microstructure have been correlated with improved electromigration performance. 11,12 Several research groups [13][14][15] have shown that plating and processing conditions have a strong influence on the texture evolution of electroplated Cu. In this article, we discuss the effect of plating current densities on self-annealing behaviors and textures of blanket electroplated Cu films.…”
mentioning
confidence: 99%